Beyond linguistic and party homogeneity: Determinants of Belgian MPs' preferences on federalism and state reform. (July 2016) - Dodeigne, Jérémy; Gramme, Pierre; Reuchamps, Min; Sinardet, Dave
Political parties are often thought of as unitary actors that have consistent preferences. This 'hidden assumption' means that heterogeneity within parties, and therefore intra-party dynamics, are overlooked in explaining attitudes. When it comes to devolution and federalisation, parties or MPs belonging to the same region are also often implicitly considered to have homogeneous viewpoints and attitudes. Relying on an original survey of MPs carried out during the Belgian political gridlock of 2010–2011, this article uncovers some of the key dimensions of the intra-party dynamics through analysis of MPs' preferences towards institutional reform in Belgium. Far from being explained along party or community lines, our results demonstrate how MPs' political and sociological background, national/regional identity, political career, and inter-community relations strongly shape their preferences.